Technology-Mediated Self-Regulated Learning and Learner Autonomy: A Qualitative Case Study of EFL Undergraduate Students - Putu Wahyu Sudewi; Andi Mega Januarti Putri; Nurul Imansari (PT. Global Research Collaboration, 2026)
The rapid growth of digital technologies has transformed English as a Foreign Language (EFL) learning, particularly in informal settings beyond the classroom. While research has extensively examined technology-enhanced language learning in formal instructional contexts, less is known about how learners in resource-constrained settings exercise autonomy and self-regulation through digital tools in everyday lives. This qualitative case study investigates how EFL undergraduate students in Majene, West Sulawesi, use digital technologies to develop autonomous English learning practices outside the formal classroom. Primary data were collected through in-depth semi-structured interviews with 12 purposively selected participants, supplemented by descriptive questionnaire data from 35 students for methodological triangulation. This study explores what types of digital platforms are selected, why they are selected, what self-regulation strategies are employed, and what challenges are faced. The results suggest that learners mainly use social media platforms (TikTok, YouTube, Instagram) and game-based language apps (Duolingo) to facilitate both incidental and intentional English learning. Thematic analysis showed three key dimensions of technology-based autonomous learning, namely: (1) Technology Selection and Motivational Orientation, (2) Self-Regulatory Strategies in Technology-Mediated Learning, and (3) Challenges and Adaptive Responses.